The Influence of Geographic Region on Hip and Knee Arthroplasty Literature From 1988 to 2018. (June 2021) - Sinclair, SaTia T.; Emara, Ahmed K.; Orr, Melissa N.; Klika, Alison K.; Piuzzi, Nicolas S.
Abstract : Introduction: Total joint arthroplasty constitutes a major focus of publications within orthopaedics. Because research expands and investigators from around the world contribute, it is important to understand the dynamics of publication. Methods: PubMed was queried for hip and knee arthroplasty-related articles published between 1988 and 2018 within seven orthopaedic journals. A bibliometric analysis was done. The manuscript region of origin was determined by the affiliated country of the last author and used to examine trends in publication. Results: A total of 6, 160 publications were included. Forty-eight countries from six continents were identified. The quantity of arthroplasty-related publications increased over the study period (n = 246 in 1988 and n = 1, 247 in 2018, P < 0.01). Articles were primarily published by North America (51.9%), Europe (32.5%), and Asia (12.4%). Clinical trials accounted for 45.6% of all publications. Articles from Asia received fewer citations than those from North America, Europe, and Oceania ( P < 0.001). Discussion: The volume of publications was five times greater in 2018 than in 1988, yet international articles constitute a marginal proportion of annual publications. Most of the literature (84.4%) originated from North America and Europe. Balanced publication of international research may favor global communication of findings, increasing the spectrum of available evidence applicable worldwide.